Arylation of Aldehydes with Indoles Using 1,3-Diisopropylimidazolinium Tetrafluoroborate as a Recyclable Catalyst for the Synthesis of Bis(indolyl)methanes in Water - Xia, Xiansong; Wei, Yingliang; Li, Anxin; Zhang, Sen; Xiao, Ziyao; Hu, Chunyan; Mao, Zewei (Synlett, 2025)
Bis(indolyl)methanes have attracted considerable attention for their interesting biological activities. Green organic-catalytic synthesis has promoted the development of green chemistry, especially in aqueous-phase reaction systems. We have developed a green and efficient catalytic arylation of aldehydes with indoles using low-cost 1,3-diisopropylimidazolinium tetrafluoroborate as a recyclable and reusable catalyst for the synthesis of bis(indolyl)methanes in water.
Keywords: organocatalysis; bisindolylmethanes; green chemistry; aqueous-phase reaction